PRINSIP-PRINSIP SYARIAH DALAM AKAD PEMBIAYAAN KPR SYARIAH PADA KOPERASI SIMPAN PINJAM PEMBIAYAAN SYARIAH BAITUL TAMWIL MUHAMMADIYAH BABAT LAMONGAN - mahmud mahmud; warsidi warsidi (Jurnal Justisia Ekonomika: Magister Hukum Ekonomi Syariah, 2021)
This study aims to prove empirically that the transaction contract and the mechanism of Sharia mortgages loan financing are carried out at BTM Mulia, Babat, Lamongan in accordance with Islamic sharia principles. This is a qualitative descriptive research, where which is focused on the study of legal actions (tasarruf), namely the implementation of mortgage loan financing at BTM Mulia with customers using murabahah contracts, and this is also called as a field research which data collection is carried out at KSPPS BTM Mulia, Babat, Lamongan. The results of this study are: (1) The implementation of the Sharia mortgages loan financing contract in BTM Mulia is in accordance with the theory of the contract which has been stipulated in Sharia Economic Law, both based on the DSN-MUI fatwas and Sharia Economic Law Compilation. (2) The implementation of Sharia mortgages loan financing (KPR) at BTM Mulia, Babat, Lamongan is in line with the sharia principles contained in Sharia Economic Law, which includes the principle of : 1). Tauhid : because the implementation of financing in BTM Mulia is not merely oriented towards the acquisition of economic benefits but more than that is to the spirit of help between human beings, 2). Justice : because there are no elements of gharar, maysir, and usury, and there are clear rights and obligations between the customer and BTM Mulia, 3). Benefit and Maslahah : because of the clear benefits and goodness, 4). Ta'awun : because if there are customers who have difficulty in installment payments, the BTM provides an extension of time for these customers to have the ability to repay their debt, 5). Khilafiyah or compliance with government regulations : because in terms of the contract procedures implemented, the mechanism that is carried out, as well as the method of resolving problems in the event of a dispute with the customer, BTM Mulia uses regulations that have been determined in Sharia Economic Law.Keywords: Sharia Principles, Transaction, Credit, Houses, BTM Mulia